Prostatic nerve subtypes independently predict biochemical recurrence in prostate cancer. (May 2019) - Reeves, Fairleigh A.; Battye, Shane; Roth, Hedley; Peters, Justin S.; Hovens, Christopher; Costello, Anthony J.; Corcoran, Niall M.
Highlights: Autonomic nerve subtypes predict cancer recurrence after prostatectomy. Our results support a regulatory role for the autonomic nervous system in prostate cancer. These findings may contribute to risk stratification and future therapeutic targets. Abstract: Objective: To describe nerve subtypes involved by perineural invasion (PNI) in prostate cancer and their relationship with clinicopathological parameters and recurrence risk. Methods: 141 prostatectomy specimens from men with localized prostate cancer and known perineural invasion were analyzed. Index tumor blocks were stained for perineural invasion and sympathetic/parasympathetic markers. For 98 patients with complete staining, nerves from up to three hotspot regions of intraprostatic perineural invasion were classified according to autonomic subtype and perineural invasion status. Findings were correlated with prospectively collected clinicopathological data. Biochemical recurrence predictors were tested in univariable and multivariable models. Results: Most intra-prostatic nerves contained sympathetic and parasympathetic fibres, irrespective of perineural invasion status. A fraction was purely sympathetic (5% PNI, 2% non-PNI) or double-negative (non-adrenergic, non-nitrergic; 1% PNI, 1% non-PNI). Perineural invasion nerve count was associated with higher pathological stage. Although total perineural invasion or non-perineural invasion nerve count did not predict biochemical recurrence, two subtypes were found to be independent predictors: pure sympathetic non-perineural invasion nerves (HR 6.79, p = 0.03) and non-adrenergic, non-nitrergic PNI nerves (HR 10.56, p < 0.005). Conclusions: Pure sympathetic nerve density without tumour invasion and perineural invasion specifically involving non-adrenergic, non-nitrergic fibres are independent predictors of biochemical recurrence post prostatectomy, supporting a role for the autonomic nervous system in prostate cancer progression.